Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702193
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Ideology and Predicting Policy Change with Social Media

Abstract: Social media has emerged as a prominent platform where people can express their feelings about social and political issues of our time. We study the many voices discussing an issue within a constituency and how they reflect ideology and may signal the outcome of important policy decisions. Focusing on the issue of same-sex marriage legalization, we examine almost 2 million public Twitter posts related to same-sex marriage in the U.S. states over the course of 4 years starting from 2011. Among other findings, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 17 publications
1
16
0
Order By: Relevance
“…As noted above, much of the research has adopted the localness assumption. For instance, this has occurred in work that seeks to describe diurnal patterns in sentiment [15], predict public health measures [9], and measure human mobility [5], among other studies (e.g., [1,8,50]). Below, we show through a case study on the work of Mitchell et al [32] what can occur if non-local VGI is filtered out of these studies.…”
Section: Social Media Vgi Based Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As noted above, much of the research has adopted the localness assumption. For instance, this has occurred in work that seeks to describe diurnal patterns in sentiment [15], predict public health measures [9], and measure human mobility [5], among other studies (e.g., [1,8,50]). Below, we show through a case study on the work of Mitchell et al [32] what can occur if non-local VGI is filtered out of these studies.…”
Section: Social Media Vgi Based Studiesmentioning
confidence: 99%
“…Indeed, researchers in HCI (e.g., [1,9,45,50]), the social sciences (e.g., [10,14,21,39,46,51]), and even the natural sciences (e.g., [38,44,49]) now regularly use social media VGI to better understand phenomena of interest ranging from social unrest and emergencies [6,24,43] to disease tracking [22,27,42].…”
Section: Introductionmentioning
confidence: 99%
“…Social media and public deliberation. Social media have become an important source for studying public's opinion on social events and political issues including gun control, same-sex marriage, racial inequality, immigration, and abortion (Benton et al, 2016;Brooker et al, 2015;De Choudhury et al, 2016;Zhang and Counts, 2015;Chung, Wei, et al, 2016). While many of these studies relied on quantitative analyses of social media content, characterized by, for example, psycholinguistic and textual features, others suggested that social media enable studies beyond quantitative opinion polling by looking into the richer social conversation and political deliberation process (Anstead and O'Loughlin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Social computing and human-computer interaction researchers have extensively studied online spaces for political discussion. For example, they have conducted observational studies on political discussions in online space, such as explorations on social media discussions during elections [115] or discussions and engagement on platforms for civic engagement [1]. Other scholars have taken more design-oriented approaches, asking how online spaces could even further support political discussions.…”
Section: Improving Political Discussion Through Digital Interfacesmentioning
confidence: 99%